2009
DOI: 10.1111/j.1471-0307.2009.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of goat cheese whey‐flavoured beverages

Abstract: Beverages made from goat cheese whey, flavoured with strawberry and peach pulp, were processed and submitted to physicochemical analysis and affective tests. The beverages exhibited similar values with respect to all the analyses of the proximate composition and little variation in pH and titratable acidity during refrigerated storage. They also showed low caloric value. For colour, aroma and consistency acceptability, there was no significant difference ( P > 0.05) among peach and strawberry flavoured samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
2
10
0
2
Order By: Relevance
“…Similarly, Tranjan et al (2009) evaluated the color, odor, consistency and taste of a beverage made from goat whey. The authors obtained lower scores that those found in the present study, mainly regarding taste.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Similarly, Tranjan et al (2009) evaluated the color, odor, consistency and taste of a beverage made from goat whey. The authors obtained lower scores that those found in the present study, mainly regarding taste.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The low scores observed in the present work, considering the employed 9‐point hedonic scale, can be attributed to the low level of sugars in the açaí pulp and to the viscosity of the final product, which is lower than that of most yogurts. Similarly, Tranjan et al () evaluated the color, odor, consistency, and taste of a beverage made from goat's cheese whey. The authors obtained lower scores than those found in the present study, mainly regarding taste, for which their peach beverage scored 5.4 and their strawberry beverage 6.2, also based on a 9‐point scale.…”
Section: Resultsmentioning
confidence: 99%
“…DIANA; PELAEZ;REQUENA, 2004;FRÍAS;FONTECHA, 2005;KYUNGWHA et al, 2007;LIM et al, 2007;SAND-STRÖM et al, 2008;CRUZ et al, 2009;TRANJAN et al, 2009;ZOELLNER et al, 2009;EVANS et al, 2010;MacLEOD et al, 2010).…”
Section: Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (Sunclassified
“…However, recently used isolation techniques for GMP production are based on chromatography, electrophoresis, and ultrafltration of caseinate/casein as peptide source (SILVA-HERNÁNDEZ et al, 2005;IKAWA;OZIMEK, 2007;SODRE DA SILVA et al, 2007;KREUS;KULOZIK, 2009;SUSIL;BRAD, 2010). Protein source and isolation method are crucial to obtain a high yield purified GMP.…”
Section: Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (Smentioning
confidence: 99%